Meningkatkan Aktivitas Dan Hasil Belajar Siswa Muatan Ips Menggunakan Model Rendang Pada Kelas V SDN Pangeran 2 Banjarmasin - Husnul Dewi Qotimah; Raihanah Sari (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The purpose of this study is to describe teacher activities, examine student activities, and determine how learning outcomes are affected. CAR is applied in this study. For the 2022/23 school year, 12 fifth grade students at Prince 2 Elementary School Banjarmasin were used as the subjects of this study. The qualitative data collected was obtained by observing the activities of students and teachers. Individual evaluation questions produce quantitative data on learning outcomes. This study uses descriptive analysis translated into tables, graphs, diagrams, percentages. The results of the study show that teachers at meetings I to IV with the "very good" criteria. Activities With very active and active qualifications, the percentage of students who meet the requirements I to IV increases to 92%. Thus, this affects the learning outcomes of meetings I-IV in the affective domain by 92%, cognitive learning by 85%, and psychomotor learning by 92%.